Cultivating leadership in early childhood education and care : trouble, complexity and promise - Gibbs, Leanne (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book redefines leadership in early childhood education, offering fresh theoretical insights and practical approaches. Delving into the challenges of the workforce in the early childhood education sector, this book unravels the narrative of leadership development. It underscores the importance of leadership practices in maintaining process quality within early childhood education (ECE), which significantly impacts children's academic, emotional, and social outcomes and life trajectories. The book presents novel conceptualisations of leadership, shedding light on factors that enable and constrain leadership development through the theoretical frameworks of complexity leadership theory and the theory of practice architectures. It also provides practical strategies for cultivating leadership within early childhood organisations. Through interviews and case studies, the book brings to life the experiences of ECE leaders, amplifying important themes and experiences. This book is an invaluable read for educators and leaders around the world, providing inspiration and guidance for their leadership journey. It is also an empirically based must-read for lecturers and students in the higher education sector"--
Keywords: Early childhood education -- Administration; Educational leadership; EDUCATION / Leadership; EDUCATION / Preschool & Kindergarten